The evolution of coloration and opsins in tarantulas. Issue 1935 (30th September 2020) - Foley, Saoirse; Saranathan, Vinodkumar; Piel, William H.
Abstract : Tarantulas paradoxically exhibit a diverse palette of vivid coloration despite their crepuscular to nocturnal habits. The evolutionary origin and maintenance of these colours remains mysterious. In this study, we reconstructed the ancestral states of both blue and green coloration in tarantula setae, and tested how these colours correlate with presence of stridulation, urtication and arboreality. Green coloration has probably evolved at least eight times, and blue coloration is probably an ancestral condition that appears to be lost more frequently than gained. While our results indicate that neither colour correlates with the presence of stridulation or urtication, the evolution of green coloration appears to depend upon the presence of arboreality, suggesting that it ptobably originated for and functions in crypsis through substrate matching among leaves. We also constructed a network of opsin homologues across tarantula transcriptomes. Despite their crepuscular tendencies, tarantulas express a considerable diversity of opsin genes—a finding that contradicts current consensus that tarantulas have poor colour vision on the basis of low opsin diversity. Overall, our findings raise the possibility that blue coloration could have ultimately evolved via sexual selection and perhaps proximately be used in mate choice or predation avoidance due to possible sex differences in mate-searching.